Utilization of some in-situ micro-organism for improving the growth and result of organic gogo rice (Oryza sativa L.) in Bengkulu coastal area - Bertham, Y. H.; Nusantara, A. D.; Arifin, Z.; Anandyawati, A. (International Journal of Agricultural Technology, 2021)
Gogo rice varieties with a high level of adaptation, and ascertain the ability of in-situ micro-organisms to increase the carrying capacity of coastal areas were investigated from July - December 2019 in Beringin Raya Village, Muara Bangkahulu District, Bengkulu City. Therefore threegogo rice varieties were obtained from BPTP Bengkulu, which are Inpago 10, Serantan and Sungggu. The results showed that the Inpago 10 had the highest adaptability compared to Serantan and Sunggu. It showed that the rhizosphere of Inpago produced Azotobacteria populations, Mycorrhizae, P-solvent and K-solvent bacteria. Furthermore, in-situmicro-organisms with double inoculation improved the rice rhizosphere characteristics and yield components compared to control